Clonal evolution and genome stability in a 2500-year-old fungal individual. Issue 1893 (19th December 2018) - Anderson, James B.; Bruhn, Johann N.; Kasimer, Dahlia; Wang, Hao; Rodrigue, Nicolas; Smith, Myron L.
Abstract : Individuals of the basidiomycete fungus Armillaria are well known for their ability to spread from woody substrate to substrate on the forest floor through the growth of rhizomorphs. Here, we made 248 collections of A. gallica in one locality in Michigan's Upper Peninsula. To identify individuals, we genotyped collections with molecular markers and somatic compatibility testing. We found several different individuals in proximity to one another, but one genetic individual stood out as exceptionally large, covering hundreds of tree root systems over approximately 75 hectares of the forest floor. Based on observed growth rates of the fungus, we estimate the minimum age of the large individual as 2500 years. With whole-genome sequencing and variant discovery, we also found that mutation had occurred within the somatic cells of the individual, reflecting its historical pattern of growth from a single point. The overall rate of mutation over the 90 mb genome, however, was extremely low. This same individual was first discovered in the late 1980s, but its full spatial extent and internal mutation dynamic was unknown at that time. The large individual of A. gallica has been remarkably resistant to genomic change as it has persisted in place.